2018
DOI: 10.1371/journal.pntd.0006216
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of inflammatory reactions during development of liver abscess in hamsters inoculated with Entamoeba nuttalli

Abstract: BackgroundEntamoeba nuttalli is an intestinal protozoan with pathogenic potential that can cause amebic liver abscess. It is highly prevalent in wild and captive macaques. Recently, cysts were detected in a caretaker of nonhuman primates in a zoo, indicating that E. nuttalli may be a zoonotic pathogen. Therefore, it is important to evaluate the pathogenicity of E. nuttalli in detail and in comparison with that of E. histolytica.Methodology/Principal findingsTrophozoites of E. nuttalli GY4 and E. histolytica SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…nuttalli have been reported in an Abyssinian colobus and Geoffroy’s spider monkey in a zoo [95,96]; and severe inflammatory reactions have been found in livers of hamsters inoculated experimentally with E . nuttalli , which indicates pathogenicity for these host species [12,15,17,97]. These findings suggest that the surface molecules of E .…”
Section: Discussionmentioning
confidence: 97%
“…nuttalli have been reported in an Abyssinian colobus and Geoffroy’s spider monkey in a zoo [95,96]; and severe inflammatory reactions have been found in livers of hamsters inoculated experimentally with E . nuttalli , which indicates pathogenicity for these host species [12,15,17,97]. These findings suggest that the surface molecules of E .…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, E. nuttalli has received attention as a potentially pathogenic and zoonotic parasite (Tachibana et al, 2009;Guan et al, 2018) (Levecke et al, 2015). Previous studies on E. nuttalli suggested that the genetic diversity of tRNA-STRs was much higher than that of the SSU rRNA gene and was signi cantly correlated with the genetic diversity of the host (Wei et al, 2018;Feng et al, 2019;Mon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…E. nuttalli is generally considered a potentially pathogenic parasite that is closely related to E. histolytica in phylogeny, its rst discovery was in non-human primates (NHPs) (Tachibana et al, 2007). Laboratory studies have found that mice inoculated with E. nuttalli developed severe in ammatory reactions and liver abscesses, which were similar to the E. histolytica infection (Tachibana et al, 2009;Guan et al, 2018). In China, E. nuttalli has only been found in wild and captive NHPs, but a previous study reported its asymptomatic infection in a zoo keeper of NHPs in Europe, therefore, E. nuttalli is considered a potential zoonotic parasite.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that IL-5 increased the number of alternatively activated macrophages and fibroblasts ( Reiman et al., 2006 ). In a hamster model of ALA caused by E. nuttalli, which is highly prevalent in macaques, alternatively activated macrophages were increased in the liver in the late stage of abscess progression ( Guan et al., 2018 ). Thus, alternatively activated macrophages augmented by IL-5 might contribute to the pathology of ALA caused by E. histolytica .…”
Section: Discussionmentioning
confidence: 99%